Code Switching in Digital Dakwah: A Sociolinguistic Study of Sheikh Fathurahman's Serambi Islami Lecture on TVRI - Aisyah, Nur; Mustofa, Izzuddin (Raja Zulkarnain Education Foundation, 2025)
This study aims to identify the forms, functions, and communicative strategies of code-switching in the sermons of Syekh Muhammad Fathurahman in the Serambi Islami program on TVRI. The research was conducted in November 2024, analyzing three sermon episodes available on the official TVRI YouTube channel. The population of the study comprises all digital sermons delivered by Syekh Fathurahman, with purposive sampling of three topics: tauhid, fiqh, and tasawwuf. Data collection instruments included transcription guidelines and linguistic annotation sheets. The data were analyzed using content analysis and sociolinguistic discourse approaches. The findings reveal that the most dominant form of code-switching is intra-sentential, followed by inter-sentential and tag switching. Code-switching serves multiple functions: authoritative-referential (quoting sacred texts and classical scholars), didactic-scientific (clarifying Islamic terminology), rhetorical-aesthetic (enhancing speech style), and cultural-modernity (adapting language for urban audiences). This research concludes that code-switching is not merely a linguistic phenomenon but a deliberate, contextual, and strategic mode of religious communication. The study’s strength lies in its triangulated analysis combining linguistic form, frequency, and function. However, the limitation stems from the small number of sermon episodes analyzed. Future research is encouraged to explore rhetorical and multimodal dimensions of Islamic digital preaching.